2005
DOI: 10.1002/ijc.21280
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection is associated with colon adenomatous polyps detected by high‐resolution colonoscopy

Abstract: Helicobacter pylori (H. pylori) is associated with the development of cancer in the stomach, but both positive and negative associations were reported with colorectal neoplasia. We sought to determine whether H. pylori is associated with colon neoplasia in Japanese population. We examined 332 patients who underwent routine high-resolution total colonoscopy and serologic testing for IgG antibodies agonist H. pylori. Subjects who received cyclooxygenase-2 inhibitors or previous eradication therapy and those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 17 publications
1
64
2
Order By: Relevance
“…Even though there were several reports that H pylori infection increased the risk of colorectal adenoma and adenocarcinoma [7][8][9] , our report reveals that H pylori infection is not a risk factor for advanced colorectal polyps, but that gastric dysplasia and an advanced age are. Thus, we infer that genetic and environmental factors probably importantly contribute to the development of advanced colorectal polyps, because patients are continuously exposed to those factors.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Even though there were several reports that H pylori infection increased the risk of colorectal adenoma and adenocarcinoma [7][8][9] , our report reveals that H pylori infection is not a risk factor for advanced colorectal polyps, but that gastric dysplasia and an advanced age are. Thus, we infer that genetic and environmental factors probably importantly contribute to the development of advanced colorectal polyps, because patients are continuously exposed to those factors.…”
Section: Discussioncontrasting
confidence: 79%
“…Several other controversial factors may increase the risk of colorectal cancer development, e.g. an increased serum gastrin level [35] , H pylori infection [6][7][8][9][10][11] and Streptococcus bovis bacteremia [36] . However, previous studies have concluded that the presence of H pylori infection and an elevated serum gastrin level are not associated with elevated risks of colorectal neoplasm development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of previous hospital-based case-control (22,23) and comparative studies (24)(25)(26)(27)(28) have reported an increased risk of colorectal neoplasia in the presence of H. pylori infection. As for CAG, two reports have described non-significant results for the correlation between colorectal cancer and CAG (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that chronic H. pylori infection promotes hypergastrinemia and that colon neoplasias also develop with an increase of gastrin serum led several authors to evaluate the possible association between the bacteria and the adenomas and adenocarcinomas of the colon. Epidemiological studies showed a greater prevalence of adenomas and/or adenocarcinomas in patients infected with H. pylori (2,5,10,11,23,24,30) . This association is, however, controversial because other researchers did not identify any association between adenomas and/or colon adenocarcinomas and infection caused by H. pylori (18,25,31,35) .…”
Section: Introductionmentioning
confidence: 99%